Impulse oscillometry in the diagnosis of obstructive ventilation disorders in pulmonary tuberculosis patients - L. D. Kiryukhina; O. S. Volodich; N. V. Denisova; N. G. Nefedova; S. A. Kovaleva; L. I. Аrchakova (Туберкулез и болезни лёгких)
Impulse oscillometry (IO) possesses certain advantages (being non-invasive and requiring no special breathing maneuvers) but fundamental differences from the well-known methods of external respiration function assessment make it difficult to introduce it into clinical practice. The objective: to evaluate specific changes in the parameters of IO in pulmonary tuberculosis patients and those with obstructive ventilation disorders. External respiration function was extensively assessed in pulmonary tuberculosis patients using IO, spirometry and body plethysmography. The classical interpretation algorithm was used and 2 groups were distinguished: 218 patients with obstructive disorders, and 90 patients without ventilation disorders. In patients with obstructive disorders, deviations of the total respiratory impedance, resistance at a frequency of 5 Hz, reactance area, and resonant frequency were the most significant. IO made it possible to identify additional disorders of mechanical properties in 11% of patients in the group without ventilation disorders according to the results of spirometry and body plethysmography. Correlation analysis in the group of patients with obstruction showed correlations of various strength between the changes in resistance and reactance with characteristics of airway obstruction assessed by traditional methods of ventilation capacity examination, and changes in static pulmonary volumes, which reflected obstructive reconstruction of the total lung capacity. OI can be used as a part of the assessment of ventilation disorders in pulmonary tuberculosis patients.